PP.33.03: ROLE OF THE WAIST/HEIGHT RATIO IN THE CARDIOMETABOLIC RISK ASSESSMENT, CLASSIFIED ACCORDING TO BODY MASS INDEX. (June 2015) - Mendonca, M.; Pereira, A.; Gomes, S.; Rodrigues, R.; Oliveira, R.; Sousa, A.C.; Henriques, E.; Freitas, S.; Ornelas, I.; Borges, S.; Pereira, D.; Reis, R. Palma Dos
Abstract : Objective: Body Mass Index (BMI) is widely used to assess the impact of obesity on cardiometabolic risk but it does not always relate to central obesity. The WHtR (waist/height), is a contant anthropometric marker of central adiposity, has been advocated as a superior indicator of cardiometabolic risk. Design and method: Cross-sectional cardiometabolic risk factor variables on 2555 adults (23.6% female and 76.4% male), 30–65 years of age were used. Based on BMI, the population was classified as obese if BMI was > 30 (n = 1759, 68.8%) and non obese if BMI < 30 (n = 796, 31.2%). The risk profiles of each group based on the WHtR (<0.6, no central obesity versus > = 0.6, central obesity) were compared. Results: 24.9% of the non obese group were centrally obese (WHtR > = 0.6) and 10.1% among the obese were not (WHtR < 0.6). 32.2% of the non Obese with Central Obesity group had Type 2 Diabetes, as compared to 15.7% of the non Obese without Central Obesity (P < 0.0001). 74.7% of the non Obese with Central Obesity had metabolic syndrome as compared to 36.7% of the non Obese without Central Obesity (p < 0.0001). On multivariate analysis the non obese with central adiposity were 1.78, 1.4, and more likely to have significant adverse levels of tryglicerides, glucose and 0.55 less times to have higher HDL, respectively. In the obese group, those without central obesity were 3.49 times likely to have significant adverse levels of HDL cholesterol (p < 0.0001), as compared to those with central obesity. Conclusions: In our population WHtR was found to further stratify cardiometabolic risk factor levels beyond BMI percentile category alone. It not only detects central obesity and related adverse cardiometabolic risk among non obese population, but also identifies those with predisposition to Glucose metabolism impairment, which has implications for primary care practice.